The Effect of Local Government Size, Fiscal Independence, Risk Management, and Internal Control Maturity on Audit Delay - Yusi Sopianti; Agus Munandar (Global Research Collaboration, 2026)
This study examines the effects of government size, fiscal independence, risk management, and internal control maturity on audit delay in Indonesian provincial governments. Audit delay reflects accountability and transparency in local government financial management. Empirical evidence on its determinants towards audit delay remains inconsistent. Using panel data from 514 regencies/ cities during 2015 to 2023, the analysis applies fixed effects regression with robust standard errors. The results show that local government size has no a positive and significant effect on audit delay, indicating that greater organizational complexity increases audit completion time. Fiscal independence, risk management, and internal control system maturity do not show significant effects. These findings suggest that structural complexity plays a more decisive role than formal governance mechanisms in explaining audit timeliness. Strengthening administrative capacity in larger governments is essential to improve the timeliness and quality of public financial reporting.